Duodenal Lipid Sensing Activates Vagal Afferents to Regulate Non-Shivering Brown Fat Thermogenesis in Rats - Clémence Blouet; Gary J. Schwartz (2012)
Previous evidence indicates that duodenal lipid sensing engages gut-brain neurocircuits to determine food intake and hepatic glucose production, but a potential role for gut-brain communication in the control of energy expenditure remains to be determined. Here, we tested the hypothesis that duodenal lipid sensing activates a gut–brain–brown adipose tissue neuraxis to regulate thermogenesis. We demonstrate that direct administration of lipids into the duodenum increases brown fat temperature. Co-infusion of the local anesthetic tetracaine with duodenal lipids abolished the lipid-induced increase in brown fat temperature. Systemic administration of the CCKA receptor antagonist devazepide blocked the ability of duodenal lipids to increase brown fat thermogenesis. Parenchymal administration of the N-methyl-d-aspartate receptor blocker MK-801 directly into the caudomedial nucleus of the solitary tract also abolished duodenal lipid-induced activation of brown fat thermogenesis. These findings establish that duodenal lipid sensing activates a gut–brain–brown fat axis to determine brown fat temperature, and thereby reveal a previously unappreciated pathway that regulates thermogenesis.